Older adults with epilepsy: memory complaints and objective neuropsychological performance - Glória Maria Almeida Souza Tedrus; Lorena Murta dos Santos; Fernanda Meneghetti (Arquivos de Neuro-Psiquiatria)
ABSTRACT Introduction: People with epilepsy frequently complain of poor memory. Objective: To assess the occurrence of memory complaints in older adults with epilepsy (OAE) and whether it is associated with clinical variables, objective cognitive performance, and quality of life (QoL). Methods: The Memory Complaint Questionnaire (MAC-Q) was related to objective cognitive performance, the Neurological Disorders Depression Inventory for Epilepsy (NDDI-E), the Quality of Life in Epilepsy Inventory (QOLIE-31), and the clinical characteristics of 83 OAE. Results: OAE showed worse cognitive performance and higher MAC-Q scores when compared to a similar control group (n=40). Impairment in multiple cognitive domains occurred in 34 (41%) OAE and was associated with older age and lower educational level. Memory complaints (MAC-Q≥25) were reported by 45 (54.2%) OAE and associated with older age, lower educational level, onset at ≥60 years, higher NDDI-E scores, lower QOLIE-31 scores, and impairment in multiple cognitive domains. Conclusions: OAE presented worse cognitive performance and greater memory complaints. Episode onset at ≥60 years of age was associated with complaints, but not with objective cognitive deficit. We found an association between subjective and objective cognitive performance, with aspects of epilepsy and worse QoL scores.